Nasogastric/Nasoenteric tube-related incidents in hospitalised patients: a study protocol of a multicentre prospective cohort study - Fernanda Raphael Escobar Gimenes; Marta Cristiane Alves Pereira; Patricia Rezende do Prado; Rhanna Emanuela Fontenele Lima de Carvalho; Janine Koepp; Ligia Menezes de Freitas; Thalyta Cardoso Alux Teixeira; Adriana Inocenti Miasso (BMJ Open)
Introduction Hospitalised patients with nasogastric/nasoenteric tube (NGT/NET) are at constant risk of incidents; therefore, healthcare professionals need to routinely monitor risks and adopt strategies for patient safety and quality of care.Aim This study aimed to evaluate the NGT/NET-related incidents in hospitalised patients and associated factors.Methods This is a multicentre study, with a prospective cohort design. Data will be collected at the general medical ward of seven Brazilian hospitals in the north, northeast, southeast and south. The sample will consist of 391 patients that require an NGT/NET during hospitalisation. Three different methods will be used to identify the incidents: (1) healthcare professionals and patients/caregivers will be required to report any NGT/NET-related incidents; (2) researchers will visit the wards to get information about the incidents with healthcare professionals and patients/caregivers; (3) the researchers will review the medical records looking for information on the occurrence of any NGT/NET-related incidents. Demographic, clinical and therapeutic details will be obtained from the medical records and will be registered in an electronic data collection tool developed for the purposes of this study. The complexity of patients will be assessed by the Patient Classification System, and the severity of comorbid diseases will be assessed through the Charlson Comorbidity Index.Implication for practice The results may encourage the use of evidence effectively to influence the scientific foundation for clinical practice and the development of evidence-based policies that will prevent, manage and eliminate complications caused by NGT/NET-related incidents, and improve the quality and safety of care provided to hospitalised patients.Ethics and dissemination The study has been approved by the Research Ethics Committee. Detailed information about the study can be provided by the principal investigator. The findings will be reported through academic journals, seminar and conference presentations, social media, print media, the internet and community/stakeholder engagement activities.